The Phenomenon of Ambivalence in Policy Implementation: How Muhammadiyah Universities Protect Women against Sexual Violence - Angin, Ria; Fauziah, Fauziah; Haerah, Kahar (Journal of Government and Civil Society, 2024)
This article discusses "The phenomenon of ambivalence in policy implementation: How Muhammadiyah / Aisyiyah Universities protect women from sexual violence". This phenomenon began when the Ministry refused to change the statement by the Council for Higher Education, Research and Development regarding the revision of article 5 (paragraph 2). ).Due to the Minister's rejection, the Rectors of Muhammadiyah/Aisyiyah as street level bureaucracy, only adopted clauses in the articles of the ministerial regulations that were in line with Islamic values and principles, and integrated them with interpretive clauses related to Article 5 (paragraph 2). ) becomes a new policy. This research uses qualitative research. The informant were the Rectors of Muhamamdiyah/Aisyiyah Universities in the Eastern part of East Java. Qualitative descriptive techniques are used to analyze the data. Each Muhamamdiyah/Aisyiyah University is currently implementing this new policy internally. Presumably because it is enforced internally, the Ministry has not banned this practice. These findings highlight the flexibility of implementing policies to protect women against sexual violence, allowing for changes in line with the internal norms and principles of street-level bureaucracy.Artikel ini membahas tentang “Fenomena ambivalensi dalam implementasi kebijakan: Bagaimana Perguruan Tinggi Muhammadiyah /Aisyiyah melindungi perempuan dari kekerasan seksual”. Fenomena ini bermula ketika Kementerian menolak mengubah pernyataan Majelis Pendidikan Tinggi, Penelitian dan Pengembangan terkait revisi pasal 5 (ayat 2). Atas penolakan Menteri tersebut, maka para Rektor Muhammadiyah/Aisyiyah sebagai street level birokrasi, hanya mengadopsi klausul dalam pasal-pasal peraturan menteri yang sejalan dengan nilai-nilai dan prinsip-prinsip Islam, serta mengintegrasikan dengan klausul penafsiran terkait dengan Pasal 5 (ayat 2). ) menjadi kebijakan baru. Penelitian ini menggunakan metode penelitian kualitatif.Informannya adalah Rektor Universitas Muhamamdiyah/Aisyiyah di Jawa Timur bagian Timur.Teknik deskriptif kualitatif digunakan untuk menganalisis data. Masing-masing Universitas Muhamamdiyah/Aisyiyah saat ini sedang melaksanakan kebijakan baru secara internal. Agaknya karena diberlakukan internal, Kementerian belum melarang praktik ini. Temuan- temuan ini menyoroti fleksibilitas penerapan kebijakan perlindungan perempuan terhadap kekerasan seksual, yang memungkinkan perubahan sejalan dengan norma dan prinsip internal birokrasi tingkat jalanan.